Community's Knowledge of Leopard Cats' Roles in the Cisokan, West Java - Erri Noviar Megantara; Teguh Husodo; Dwi Rustam Kendarto; Asep Zainal Mutaqin; Sya Sya Shanida; Indri Wulandari (UPT Publikasi Ilmiah UNISBA, 2024)
Local communities have ways of managing and utilizing forest products, including leopard cats' habitat. Communities have knowledge and perceptions passed down from one generation to the next through community participation in their environment. This activity aims to reveal the community's knowledge regarding the role of leopard cats in the Cisokan. The implementation of this activity consists of collecting issues and data, FGD, and evaluation. The results show that almost all informants do not know the role of leopard cats in controlling prey animal populations and agricultural pests. Although leopard cats prey on domestic birds, they are not considered a nuisance to the community. After a joint discussion with the community regarding the ecological role of leopard cats, 79% of informants understood leopard cats' role in nature, which indirectly supported agriculture. Besides that, 70% of respondents understand that leopard cats should be protected.